Left bundle branch area pacing in patients with severe interventricular septal hypertrophy: A multicenter study assessing feasibility, safety, and outcomes of lumenless and stylet-driven leads - Sanjai Pattu Valappil, MD, DM; Abhinav B. Anand, MD, DM; Anindya Ghosh, MD, DM; Krishnaswamy Subramanyan, MD, DM; Pramod Jaiswal, MD, DM; Krishnan Jayanthi, MD, DNB; Golla N. Prasad, MD, DNB; Tirupattur S. Srinath, MD, DNB; Shilpa Menon, MD, DM; Sharan Shreedhar, MD; Karthikeyan D, DMRD, DNB, Radiology; Velayudhan Bashi, MS, MCH; et al. (Heart Rhythm O2)
Background: There has been limited success using left bundle branch area pacing (LBBAP) in patients with severe interventricular septal hypertrophy (IVSH). Objective: This study assesses the feasibility, safety, and outcome of LBBAP in patients with severe IVSH. Methods: 19 adult patients with severe IVSH who underwent LBBAP were enrolled. Baseline patient characteristics, procedural data, and postprocedural results were collected. The feasibility of LBBAP in patients with severe IVSH using the lumenless leads (LLL) and stylet-driven leads (SDL) were analyzed. Results: 19 IVSH and 529 normal septal thickness (NST) patients underwent LBBAP. Implant success was achieved in 497 patients with NST (93.9%) and 14 patients with severe IVSH (73.6%). Among the 19 patients with severe IVSH, 7 patients underwent attempted LBBAP using LLL, with successful outcomes in 4 (57.1%). The remaining 12 patients underwent LBBAP with SDL, of which 10 were successful (83.3%). Mean septal thickness (20 ± 1.9 vs 21 ± 2.2), paced QRS duration (123 ± 17 vs 121 ± 9), and left ventricular activation time (LVAT) (75 ± 6 vs 74 ± 9) were comparable in the LLL and SDL groups. The lead thresholds (0.8 ± 0.3) remained stable over the mean follow-up duration of 36 ± 28.67 months without any lead-related complications. Conclusion: LBBAP in patients with severe IVSH is safe and feasible. Although the overall success rates in this subgroup were lower (73.6%) compared with patients with NST, this was not significantly different with the use of SDL (83.3%) (P = .15).